Treatment of polyamide 66 fabric for increased ultraviolet protection. Issue 15 (August 2020) - Rietzler, Barbara; Caven, Barnaby; Bechtold, Thomas; Pham, Tung
We reported previously that treatment of polyamide 66 with a mixture of CaCl2 /EtOH/water results in a significant increase of surface roughness. A higher surface roughness is correlated with greater light scattering propensity, and therefore we investigated if polyamide 66 fabrics treated with the mixture exhibit lower ultraviolet (UV) transmission. The work was performed on a commercially available plain-woven polyamide 66 fabric, and the UV protection factor (UPF) increased from a value of 25 (of the fabric as received) to >100 (after a 1-min treatment with the mixture). There was no significant change in cover factor of the fabric. As the solvent mixture is environmentally benign and the desired effects are obtained with short treatment times, we believe this process may be a more sustainable alternative to the use of UV absorbers that is the state-of-the-art technology at the present time. In this paper, we have described the treatment and its effects on substrate topography and mechanical properties.